Bifurcation solitons, Y-type, distinct lumps and generalized breather in the thermophoretic motion equation via graphene sheets - Seadawy, Aly R.; Ahmad, Ali; Rizvi, Syed T.R.; Ahmed, Sarfaraz (Alexandria engineering journal, 2024)
Learned from wrinkle wave motions, we concentrated on bifurcation phenomena in substrate-supported graphene sheets by obtaining the bifurcation solitons of thermophoretic motion equation. We find new soliton solutions by applying the bilinear technique and correctly choosing the auxiliary function involved in the bilinear form. Use of the Hirota bilinear technique combined with symbolic computation yields lump solutions as well as lump-type solutions. The governing model is subject to computation of the lump one strip, lump two strip, Y-type, lump periodic solution, generalised breather, and lump periodic solution. When simulating waves in different physical systems, such as water waves, fibre optics, and plasma physics, lump and lump type solutions are crucial. Rogue waves are studied in relation to large and unforeseen ocean wave phenomena that might affect coastal buildings and ship safety. In communication systems, including optical fibres, generalised breathers are used to comprehend and regulate pulse propagation.